Faktor Penentu Profitabilitas Perusahaan di Sektor Basic Material Bei - Hendra, Hendra (Jurnal Akuntansi, 2024)
This article is arranged to describe the impact of several predictor/independent variables to profitability. The predictors variable which use in this investigation are: Working Capital Turnover (WCTO), corporation size, growth of sales (GROWTH), leverage (DER) and liquidity (CR) to profitability proxied by ROA. The basic material company that listed in Indonesian Stock Exchange for period 2012-2022 is the population of this study. The purposive sampling method carried out consisted of ten basic material corporations with a total data of 110. This research test uses regression panel analysis in hypothesis examination. The firm size is only variable that affects profitability. While other predictor variables named working capital turnover, sales growth, leverage, and liquidity has no impact to profitability. Keywords: Firm Size, Liquidity, Leverage, Profitability, Sales Growth, Working Capital Turnover